DIVA : lesbian life & style. (London : Millivres, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks ; vanaf (1998) : maandelijks
Redactie : 116-134 Bayham Street, London NW1 OBA
Engels
Periodiek